2002
DOI: 10.1002/app.10168
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationships of poly(urethane urea)s with ultra‐low monol content poly(propylene glycol) soft segments. I. Influence of soft segment molecular weight and hard segment content

Abstract: Structure-property relationships in poly(urethane urea)s synthesized with ultra-low monol content poly(propylene glycol) soft segments were investigated as soft segment molecular weight (2000, 4000, and 8000 g/mol) and hard segment content (6.3 and 9.0 wt %) were varied. Morphological features such as interdomain spacing and interphase thickness were quantified and revealed with small-angle X-ray scattering (SAXS) and atomic force microscopy (AFM). The thermal and mechanical behavior was assessed with a dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
84
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 37 publications
10
84
0
Order By: Relevance
“…Thus, for the imaged PUs, the microdomains appear lighter whereas darker regions correspond to the softer polyol phase. 16,17 Figure 21 shows the microphase of polybutadiene-PU. The existence of brighter areas demonstrated that the hard and soft segments did not possess homogeneous features and demonstrated phase separation in the PU elastomer.…”
Section: Afm Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for the imaged PUs, the microdomains appear lighter whereas darker regions correspond to the softer polyol phase. 16,17 Figure 21 shows the microphase of polybutadiene-PU. The existence of brighter areas demonstrated that the hard and soft segments did not possess homogeneous features and demonstrated phase separation in the PU elastomer.…”
Section: Afm Analysismentioning
confidence: 99%
“…16 The thermal properties of MRE were also investigated by step-scan DSC. A comparison of MREs and PU elastomers is provided in Figure 18.…”
Section: Figure 21mentioning
confidence: 99%
“…First, a soft segment (SS) prepolymer, end-capped with diisocyanate is prepared with excess diisocyanate. [11][12][13] This prepolymer is subsequently extended with an extender and possibly also additional diisocyanate. For thermoplastic elastomer applications, the diisocyanate, MDI 4,4 0 methylenebis(phenyl isocyanate) is often used, and in order to obtain copolymers with good low temperature properties, poly(propylene oxide) (PPO) is generally employed since PPO is noncrystalline.…”
Section: Introductionmentioning
confidence: 99%
“…[14] When an MDIendcapped prepolymer with a low concentration of free MDI is reacted with a diamine, the result is urethane-urea HS with a narrow length distribution. [12] If additional MDI is added together with the diamine, the HS length distribution becomes random. [13] Generally, the melting temperature of the HSs increases rather significantly as their length increases.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Factors that influence the degree of phase separation include soft segment molecular weight, hard and soft segment chemistries, and the hard to soft segment ratio. [20][21][22][23][24] Segmented block copolymers utilized for biomedical applications have traditionally been intended for long-term use. Thus, new biodegradable formulations are needed to translate this family of biomaterials to tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%